Molecular Analysis and Adaptation Test of Code-qTSN4 and Code-qDTH8 Rice Lines - nFN Tasliah; nFN Ma'sumah; Joko Prasetiyono (Jurnal AgroBiogen, 2019)
Rice lines for increasing grain yield derived from Code variety that have loci associated to the spikelet number and early heading date (qTSN4 and qDTH8 locus, respectively) have been developed. The objectives of this research were to molecularly analyze, to evaluate the yield of Code-qTSN4 and Code-qDTH8 lines in the field, and to obtain the lines with yield potential of at least 10% higher than that shown by Code. The study was conducted in October 2016 to March 2017. The study was divided into two activities: molecular verification of the qTSN4, qDTH8, and Xa7 loci using specific markers and field trials at two locations in West Java, i.e. Sukamandi Experimental Station and Cianjur farmer’s paddy field. The genetic materials used were 56 rice genotypes consisted of 49 lines (Code-qTSN4 and Code-qDTH8) and 7 check varieties. Molecular analysis showed that all rice lines tested contained qTSN4, qDTH8, and Xa7 loci. All of the loci were in homozygous stage indicating that they were pure lines. Field trial results showed that Cianjur location gave much better on yield component variables than that in Sukamandi. The highest increase in spikelet number was shown by B6-4 planted at Cianjur with increase of 30.06% and B12-2 planted at Sukamandi with increase of 25.15% compared to Code. Both lines were classified as Code-qTSN4 line group. The qTSN4 and qDTH8 loci proved to increase yield more than 20% compared to Code. A total of 34 lines resulted from this study can be used for advanced yield trials conducted at several agro-ecologically different locations.